Perbedaan Pelaksanaan Kegiatan Esktrakurikuler di Sekolah Negeri Sukapira I Kota Cirebon dan Sekolah Juara Wirautama Patrol Indramayu - Ninik Sugiyarti; Muhammad Ghaffar Rasyad; Asep Mulyana (LP3M IAI Al-Qolam, 2025)
Through extracurricular activities, which are non-academic endeavors, students can channel and develop their interests and talents in order to increase their knowledge and skills. At Sukapura 1 School and Patrol School Juara Wirautama Indramayu, extracurricular activities include scouting, silat, karate, taekwondo, angklung, dance, fine arts, study clubs, and sports. Since scouts are one of the government-sponsored programs, along with Paskibra and the Red Cross Youth, they must take part in extracurricular activities, however, there is definitely a difference in how these are organized or carried out in each school. To gather data regarding the disparity between Juara Wirautama Indramayu Patrol School and Sukapura I School's extracurricular activities, Techniques from interviews and observation are used in this study. After that, the data is transformed into information. This study shows that Wirautama Patrol Champion School increases dominant potential in every field, whereas Sukapura 1 School in Cirebon City itself enhances national and cultural values. The characteristics of these two schools differ. Nonetheless, both organizations strive to guarantee that extracurricular activities have a beneficial impact on students' development.